Temporal variation of Manning roughness coefficient in furrow irrigation and its relationship with various field parameters - Rad, Hadi Rezaei; Ebrahimian, Hamed; Liaghat, Abdolmajid; Khalaji, Fatemeh; Arani, Mahshid Shabani (Applied water science, 2025)
This research aimed to ascertain the Manning roughness coefficient ( n ) and explore the impact of various factors on it across different phases and irrigation events. The Manning’s n for furrow irrigation was determined in the advance, storage, and whole irrigation phases utilizing the SIPAR_ID model, Manning equation, and WinSRFR software, respectively. Parameters affecting the Manning’ n were identified through Pearson and Kendall tests. The study involved measuring the Manning’s n under six distinct inflow rates, classified as low and high flows. Three irrigation events (first to third), advance and storage phases, two irrigation intervals, and two soil textures (Clay loam and Silty clay loam) were considered. Results indicated that the Manning’s n ranged from 0.017 to 0.636, 0.015 to 0.317, and 0.015 to 0.34 in the advance, storage, and whole irrigation phases during the first to third irrigation events, with mean values of 0.083, 0.054, and 0.055, respectively. Higher roughness coefficients were observed in the advance phase. Additionally, findings suggested that if the advance phase is short relative to the total irrigation time, the Manning’s n from the advance phase can be applied to the whole irrigation event without separate consideration for storage phase roughness. Pearson and Kendall statistical tests revealed that the Manning roughness coefficient during the entire irrigation event was strongly correlated with advance time (r = 0.65, p < 0.01) and moderately correlated with inflow and outflow rates, as well as initial soil moisture and cross-sectional flow area. A weak correlation was observed between the roughness coefficient and the furrow slope (r = 0.238). During the storage phase, advance time had the strongest positive correlation with roughness, while inflow rate had a weak negative correlation (r = −0.31).